In vivo analysis of MT-based vesicle transport by confocal reflection microscopy. - Gáspár, I.; Szabad, J. (Cell Motility and the Cytoskeleton, 2009)
The use of confocal reflection microscopy (CRM) for the in vivo analysis of microtubule (MT) mediated transport of lipid droplets in the developing Drosophila egg primordia is described here. The developing Drosophila oocytes are ideal objects to study MT-mediated transport in vivo: transport of e.g. the lipid droplets can be conveniently, selectively and sensitively monitored through CRM and the egg primordia are readily available for physical, chemical and/or genetic manipulations. CRM is a non-destructive way to follow vesicle movement and allows high frame rate image recording. When combined with fluorescence imaging, CRM offers simultaneous visualization of the cargo and the protein(s) of interest, i.e. a motor or a cargo adapter, thus allowing a better understanding of MT-mediated transport and spatiotemporal coordination of the transport machinery.